Improving Activity of Lycium Barbarum. Polysaccharide on Depressive Mice Induced by Reserpine - Zhao, Rui (Iran J Pharm Res, 2019)
Depressive disorder will be the second highest disease burden worldwide, which will impair life quality, reduce productivity, and increase disability and mortality. Lycium barbarum. polysaccharide (LBP) is the main active fraction purified from Lycium barbarum. The aim of this study was to evaluate the potential therapeutic effects of LBP on depressive mice induced by reserpine, as well as the relevant mechanisms. The antidepressant effect of LBP was investigated by open field test (OFT), forced swimming test (FST), tail suspension test (TST), and antagonism of reserpine hypothermia and ptosis in mice. In addition, we examined the oxidative status and antioxidation power of striatum in both control and depressive mice with or without LBP treatment. To explore the mechanism of LBP on regulating antioxidants in the depressive mice, we detected the expression level of Bcl-2 and poly (ADP ribose) polymerase (PARP) in striatum of mice by western blotting. The results showed that administration with LBP for 4 consecutive weeks significantly increased locomotor activity, reduced the duration of immobility, and antagonized hypothermia and ptosis in mice induced by reserpine. Also, LBP treatment was able to reduce the lipid peroxidation (LPO) production, and enhance the antioxidation effect of the striatum in depressive mice. Furthermore, LBP inhibited the decreased extent of the apoptotic suppressors, Bcl-2 and PARP, which were markedly decreased after treatment with reserpine. The above results indicated that LBP possess antidepressant activities, probably via its powerful antioxidative properties and then decreased the apoptosis of striatum neuron.